Early and Late Mineralization of the Intrusive Rocks in Lokpaukwu, Southern Benue Trough, Nigeria. - Onwualu-John, J. N.; Nwosu, J. I. (European Journal of Applied Sciences, 2021)
The intrusive rocks (dolerites) in Lokpaukwu were studies to evaluate the kind of mineralization in them. The dolerites erupted at three regions in the Lokpaukwu area (Eziama, Eluama, Umuchieze). The results of the petrographic studies show that the dolerites in Eziama, Eluama, are characterized by olivine, pyroxene, plagioclase, biotite, hornblende, hematite. The first pattern of mineralization of the dolerites at LokpaUkwu appears to start from the Eziama or Eluama region, the dolerites of these two regions conforms to the mineralization of dolerites that exist in some other parts of the southern Benue trough. Umuchieze dolerites have some peculiarities that differentiate it from other dolerites of the Southern Benue trough. The second pattern of mineralization exist in dolerites of umuchieze which are characterized by quartz, pyroxene, plagioclase, biotite, and hematite. These phenomena indicate that two types of dolerites exist in LokpaUkwu area, the Olivine dolerites and the quartz porphyry dolerites. The interaction of the magma with sedimentary host rocks or hydrothermal influx or late stage of crystallization of magma probably played vital roles in the formation of the quartz porphyry dolerites, whereas the olivine dolerites may have originated from early stage of crystallization of basaltic magma. The basaltic magma that gave rise to these rocks(dolerites) probably has a single source region but erupted at different rifts which gave opportunity for some magmatic evolutionary processes (fractionation, contamination, assimilation) to play major roles.